1996
DOI: 10.1159/000237370
|View full text |Cite
|
Sign up to set email alerts
|

Oleaceae Pollinosis: A Review

Abstract: In the Oleaceae family, the most allergenic pollen is produced by Olea europaea, the olive tree, which in the Mediterranean area has been recognized as one of the most important cause of seasonal respiratory allergy The olive pollination season lasts from May to the end of June and sometimes causes severe symptoms (oculorhinitis and/or bronchial asthma). Olive pollinosis is quite rare in the form of monosensitization. Although adults are affected the most, olive sensitization can be recognized in children, too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(72 citation statements)
references
References 23 publications
(27 reference statements)
1
69
0
2
Order By: Relevance
“…Olive tree (Olea europaea) pollen is a main cause of seasonal respiratory allergy in Mediterranean countries and other areas (Liccardi et al 1996). To date, 10 allergens from olive pollen, Ole e 1-Ole e 10, have been characterized (Rodríguez et al 2002;Barral et al 2004), but only the three-dimensional (3D) structure of Ole e 6 has been determined (Treviño et al 2004).…”
mentioning
confidence: 99%
“…Olive tree (Olea europaea) pollen is a main cause of seasonal respiratory allergy in Mediterranean countries and other areas (Liccardi et al 1996). To date, 10 allergens from olive pollen, Ole e 1-Ole e 10, have been characterized (Rodríguez et al 2002;Barral et al 2004), but only the three-dimensional (3D) structure of Ole e 6 has been determined (Treviño et al 2004).…”
mentioning
confidence: 99%
“…Moreover, the pollen season was found to be longer in the air traps compared to the flowering phenological observations. Other studies have also demonstrated a long period of olive pollen grains in the air compared to the flowering period of the trees (Gioulekas et al, 1991;Liccardi et al, 1996;Minero and Candau, 1997;Fornaciari et al, 2000;Altintas et al, 2004;Gioulekas et al 2004a, b). Meiffren (1988) and Fornaciari et al (2000) have reported the ability of olea pollen to travel over middle and long distances.…”
Section: Discussionmentioning
confidence: 89%
“…Measurements of flowering phenology were carried out daily from May to June in 2008 and 2009, when the flowering period of O. europaea in the area occurs (Liccardi et al, 1996). Six trees that belonged to the most cultivated variety in the area and four trees that belonged to the remaining four varieties were randomly selected.…”
Section: Phenological Datamentioning
confidence: 99%
“…In the Oleaceae family, the most allergenic pollen is produced by Olea europaea, the olive tree, which in the Mediterranean area has been recognized as being one of the most important causes of seasonal respiratory allergy (11). There is a growing body of evidence that components of air pollution interact with inhalant allergens carried by pollen grains and may enhance the risk of both atopic sensitization and exacerbation of symptoms in sensitized subjects (14,15), since urban air pollution affects both airborne allergenic pollen and the airways of exposed subjects.…”
Section: P Judaica Grows In Coastal Mediterranean Areas Such As Spaimentioning
confidence: 99%